Practice Comparison and Cost Analysis of Direct-to-Consumer Telemedicine Platforms Offering Testosterone Therapy. Issue 11 (9th June 2022) - Jesse, Erin; Sellke, Nicholas; Rivero, Marco-Jose; Muncey, Wade; Ghayda, Ramy Abou; Loeb, Aram; Thirumavalavan, Nannan
Abstract: Background: Direct-to-consumer telemedicine platforms have expanded their reach to include services for the evaluation and treatment of testosterone deficiency. Aim: We aim to (i) evaluate the treatment practices and costs associated with receiving testosterone therapy through direct-to-consumer telemedicine platforms; (ii) compare these practices to the American Urological Association guidelines; and (iii) compare the cost of receiving similar care at a tertiary center. Methods: Google was queried to identify telemedicine platforms offing testosterone therapy. Websites were analyzed for information regarding the initial consultation, initial laboratory evaluation, follow up, treatment monitoring regimen, and associated costs of receiving testosterone therapy. The costs for similar services at a tertiary care center were estimated using a single institution's online cost estimator for a patient with no insurance, private insurance, or Medicare. Outcomes: Evaluation and treatment practices of each platform were compared to the American Urological Association guidelines, and a cost analysis was completed for the cost of (i) undergoing an initial evaluation, and (ii) receiving 12 months of treatment through each platform and at a tertiary center. Results: Three online platforms met inclusion criteria: Hone, Regenex Health, and TRT Nation. The initial evaluation and follow up of patients on TTh were similar between the online platforms and practice guidelines. The costs of the initial consultation were lowest for the patient with Medicare at a tertiary center and via the telemedicine platforms. Conversely, the cost of 12 months of intramuscular testosterone treatment was highest via the telemedicine platforms, ranging from $1, 586 to $4, 200, as compared to the tertiary center, which ranged from $134.01 to $1, 333.04 with varying insurance models. Costs of ongoing treatment with transdermal testosterone are similarly higher via DTC platforms. Clinical Implications: Patients with private insurance or Medicare should be counseled that ongoing treatment through telemedicine platforms will likely incur a greater cost than receiving such care at a tertiary center that can utilize insurance coverage. Strengths & Limitations: Practice and cost comparisons include accurate, up-to-date information based on each platform's website. Limitations include the analysis of only three telemedicine platforms, and the ability to describe only the information provided on each website. In addition, cost estimates for the tertiary center only include a single type of private and public insurance, limiting generalizability. Conclusion: This observational study indicates that direct-to-consumer telemedicine platforms are largely following practice guidelines in the evaluation and treatment of testosterone, however, there is a high cost associated with ongoing treatment.